A Study on Cotton Seeds in Rural Market with Reference to Nalgonda District (A.P.) - Venkat Ramana Reddy, M. (Indian Journal of Marketing, 2005)
Cotton is fiber crop. It is one of the important commercial crops in India. It occupies an important place in the Indian economy. It is an important earner of foreign exchange. Its cultivation provides employment to 16 million people. The cotton plant yields cotton fiber and cottonseeds. The fiber is important raw material for the textile industry. Cottonseeds yields edible oil and also cake suitable for the folder. The Cottonseeds oil is largely used in the vanaspati Industry. Thus cotton is rightly described as "White Gold". It has been aptly called the "Universal Fiber".